Cross-sectional Association between Walking Pace and Sleep-disordered Breathing - Suri, S. V.; Batterham, A. M.; Ells, L.; Danjoux, G.; Atkinson, G. (International Journal of Sports Medicine, 2015)
Sleep-disordered breathing is an important comorbidity for several diseases, including stroke. Initial screening tools comprise simple yes/no questions about known risk factors for sleep-disordered breathing, e. g., obesity, sex. But walking speed has not been investigated in this context. We examined the cross-sectional association between walking pace and sleep-disordered breathing in the population-level Multi-Ethnic Study of Atherosclerosis. A sample of 2 912 men and 3 213 women (46–87 years) reported perceived walking pace outside their homes. A walking pace<0.89 m/s was deemed “slow”, with ≥ 0.89 m/s considered “average/brisk” according to validated thresholds. Sample prevalences were: sleep apnoea (3.5%), self-reported apnoeas (8.4%), loud snoring (20.5%), daytime tiredness (22.2%) and slow-walking pace (26.9%). The 95% CI risk differences (multivariable-adjusted) for slow vs. faster walking pace were; sleep apnoea (0.4–2.5%), self-reported apnoeas (0.1–3.8%), loud snoring (1.2–8.3%), and daytime tiredness (3.0–7.8%). Risk differences were similar between sexes. The multivariable-adjusted risk ratio indicated that slower walkers had 1.5 (95% CI: 1.0 to 2.1) times the risk of sleep apnoea vs. faster walkers. In conclusion, a slower walking speed was associated with a greater prevalence of sleep-disordered breathing, independently from other common screening factors. Therefore, a simple walking speed question may help consolidate screening for this disorder.
Keywords: obstructive sleep apnoea; physical activity; screening; frailty